Three-dimensional finite-time optimal cooperative guidance with integrated information fusion observer - Yiao Zhan; Linwei Wang; Di Zhou (Defence Technology)
Intercepting high-maneuverability hypersonic targets in near-space environments poses significant challenges due to their extreme speeds and evasive capabilities. To address these challenges, this study presents an integrated approach that combines a Three-Dimensional Finite-Time Optimal Cooperative Guidance Law (FTOC) with an Information Fusion Anti-saturation Predefined-time Observer (IFAPO). The proposed FTOC guidance law employs a nonlinear, non-quadratic finite-time optimal control strategy designed for rapid convergence within the limited timeframes of near-space interceptions, avoiding the need for remaining flight time estimation or linear decoupling inherent in traditional methods. To complement the guidance strategy, the IFAPO leverages multi-source information fusion theory and incorporates anti-saturation mechanisms to enhance target maneuver estimation. This method ensures accurate and real-time prediction of target acceleration while maintaining predefined convergence performance, even under complex interception conditions. By integrating the FTOC guidance law and IFAPO, the approach optimizes cooperative missile positioning, improves interception success rates, and minimizes fuel consumption, addressing practical constraints in military applications. Simulation results and comparative analyses confirm the effectiveness of the integrated approach, demonstrating its capability to achieve cooperative interception of highly maneuvering targets with enhanced efficiency and reduced economic costs, aligning with realistic combat scenarios.